The Psychological Impact of COVID-19 in Italy: Worry Leads to Protective Behavior, but at the Cost of Anxiety - Prete, Giulia; Fontanesi, Lilybeth; Porcelli, Piero; Tommasi, Luca (Frontiers in Psychology, 2020)
The World Health Organization defined COVID-19 as a pandemic on March 11th, due to the spread of the new SARS-CoV-2 coronavirus in all continents. Italy had already witnessed a very fast spread, that brought the Government to place the entire country under quarantine on March 11th, and reaching more than 30,700 fatalities in two months. We hypothesized that pandemic and related compulsory quarantine would lead to an increase of anxiety state and protective behaviors to avoid infections. We aimed to investigate whether protective behaviors might have been enhanced or limited by anxiety and emotional reactions to previous experience of stressful conditions. We collected data from 618 Italian participants, by means of an online survey. Participants were asked to rate their level of worry for the pandemic, and to complete two questionnaires measuring the anxiety level: the State-Trait Anxiety Inventory (STAI-Y) and the Pre-traumatic stress reaction checklist (Pre-Cl). Finally, respondents were also asked to report about their compliance with protective behaviors suggested to avoid the spread of the virus (e.g., washing hands). Results show that respondents with higher levels of worry reported higher levels of anxiety and pre-traumatic reactions, with positive correlations among the three measurements, and that higher frequency of the three protective behaviors were put in place by respondents with higher levels of worry. Moreover, regression analysis showed that worry for COVID-19 was most predicted by age, anxiety levels and Pre-traumatic stress. These results could be interpreted in an evolutionary framework, in which the level of worry leads persons to become more cautious (protective behaviors) maximizing long-term survival at the cost of short-term dysregulation (anxiety).